Law No. 25 of the Year 2020 On Increasing the Variable Wage Pension, As Regards the Special Raises Prescribed As of 1/7/2006 But Not Added to the Basic Wage on the Pension Entitlement Date, and Amending Certain Provisions of the Social Insurance and Pensions Law, Promulgated by Law No. 148 of the Year 2019 = قانون رقم 25 لسنة 2020 بزيادة معاش الأجر المتغير عن العلاوات الخاصة التى تقررت بدءاً من 1/7/2006 ولم تضم إلى الأجر الأساسى فى تاريخ استحقاق المعاش وتعديل بعض أحكام قانون التأمينات الاجتماعية والمعاشات الصادر بالقانون رقم 148 لسنة 2019 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic